2019
DOI: 10.1021/acsmacrolett.9b00182
|View full text |Cite
|
Sign up to set email alerts
|

Ugi Three-Component Polymerization Toward Poly(α-amino amide)s

Abstract: Due to their great modularity, ease of implementation, and atom economy, multicomponent reactions (MCRs) are becoming increasingly popular macromolecular engineering tools. In this context, MCRs suitable in polymer synthesis are eagerly searched for. This work demonstrates the potential of the Ugi-three component reaction (Ugi-3CR) for the design of polymers and, in particular, of poly(α-amino amide)s. A series of polymers containing amino and amido groups within their backbone were obtained through a one-pot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 68 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…[ 1,2 ] Compared with classic polymerization approaches, MCPs enjoy great structural diversity of products, strong designability of reaction procedure and product structure, mild reaction condition, simple monomer structures, environmental benefits, and so on. [ 3–6 ] Besides the most widely explored isocyanide‐based MCPs including Passerini three‐component polymerization (3CP) of isocyanide, carboxylic acid and oxo‐component (ketone or aldehyde), [ 7–10 ] and Ugi four‐component polymerization (4CP) of isocyanide, carboxylic acid, oxo‐component (ketone or aldehyde) and amine, [ 11–13 ] alkyne‐based MCPs were extensively reported in the past few years, [ 14–16 ] owing to the rich chemistry of alkynes and the unsaturated product structures with potential optoelectronic properties from alkyne chemistry, [ 17 ] which could be applied in optoelectronic devices, [ 18,19 ] or as luminescent materials, [ 14,20 ] and antibacterial materials. [ 21 ]…”
Section: Figurementioning
confidence: 99%
“…[ 1,2 ] Compared with classic polymerization approaches, MCPs enjoy great structural diversity of products, strong designability of reaction procedure and product structure, mild reaction condition, simple monomer structures, environmental benefits, and so on. [ 3–6 ] Besides the most widely explored isocyanide‐based MCPs including Passerini three‐component polymerization (3CP) of isocyanide, carboxylic acid and oxo‐component (ketone or aldehyde), [ 7–10 ] and Ugi four‐component polymerization (4CP) of isocyanide, carboxylic acid, oxo‐component (ketone or aldehyde) and amine, [ 11–13 ] alkyne‐based MCPs were extensively reported in the past few years, [ 14–16 ] owing to the rich chemistry of alkynes and the unsaturated product structures with potential optoelectronic properties from alkyne chemistry, [ 17 ] which could be applied in optoelectronic devices, [ 18,19 ] or as luminescent materials, [ 14,20 ] and antibacterial materials. [ 21 ]…”
Section: Figurementioning
confidence: 99%
“…methanol, ethanol, TFE) [45,46,49,54,56,57] but quite often other solvents are employed such as dichloroethane, [58] toluene, [52,59,60] dimethyl-formamide, [61] mesitylene (1,3,5-trimethylbenzene) [51] and ethyl acetate [47] due to solubility issues. [61] Frequently, the U-3CR is reported as the side reaction of the classical Ugi reaction (U-4CR), where the acid component plays the role of the catalyst. The U-3CR, often, proceeds with the aid of a diversity of catalysts, therefore, the applicability of the U-3CR is somewhat lowered in comparison with the U-4CR.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…The first U-3CR protocol for the synthesis of macromolecules based in α-aminoamide backbone was developed in 2019 by Debuigne et al [61] (Scheme 36). The group selected to apply phenyl phosphinic acid (PPA) as an U-3CR catalyst based on the study reported by List et al [52] Since their experiments (Debuigne et al) would include poly(α-aminoamides) 62 synthesized by aromatic monomers, the group selected DMF as a solvent rather than toluene (used by List et al) to achieve better solubility.…”
Section: Polymers Based On U-3crsmentioning
confidence: 99%
“…Because multiple components are able to react in one‐step to high‐efficiently generate predictable architectures and functionalities under mild reaction conditions. [ 1–8 ] Noteworthy, the key for successful MCRs is to seek highly efficient “click reaction” (Passerini reaction, [ 9 ] Ugi reaction, [ 10,11 ] Biginelli reaction, [ 12,13 ] and Kabachnik‐Fields reaction [ 14 ] ) that can be carried out in one‐step and one‐pot without the generation of side products. Therefore, MCRs also exhibit unique click properties as the typical Cu(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) reaction, [ 15–17 ] such as high atom economy and simple procedure.…”
Section: Figurementioning
confidence: 99%